1987
DOI: 10.1159/000180692
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Parameters in Graves’ Disease: Are They Useful for Indication and Monitoring of Antithyroid Drug Treatment?

Abstract: This paper reviews the available published data on studies of a correlation between the presence or intensity of measurable immunological abnormalities or markers in Graves’ disease and the outcome after a course of antithyroid drug. The following parameters are discussed: circulating anti-thyroid-stimulating hormone receptor antibodies; antitubulin antibodies; human lymphocyte antigens, and repartition of T-lymphocyte subsets. At the present time no single parameter has any real practical value for individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The value of the prognostic markers used to predict the outcome of Graves' hyperthyroid patients treated with antithyroid drugs (ATD) has been questioned (1,2). Increased risk of relapse in patients who are positive for serum thyroidstimulating antibody (TSAb) at the end of treatment has been shown (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of the prognostic markers used to predict the outcome of Graves' hyperthyroid patients treated with antithyroid drugs (ATD) has been questioned (1,2). Increased risk of relapse in patients who are positive for serum thyroidstimulating antibody (TSAb) at the end of treatment has been shown (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Increased risk of relapse in patients who are positive for serum thyroidstimulating antibody (TSAb) at the end of treatment has been shown (3)(4)(5). However, patients without detectable TSAb activ¬ ity have also relapsed, decreasing the value of this parameter (1,5,6). The correlation between serum thyroglobulin (Tg) levels and either TSAb or T3 suppressibility in patients who remitted after ATD therapy suggested that the serum Tg could substitute for TSAb or T3 suppression tests (7).…”
Section: Introductionmentioning
confidence: 99%
“…This mild form of GD is characterized by a small goiter, the (near) absence of signs of ophthalmopathy or dermopathy, and the ab sence of a previous attack of GD. In addition to these clinical features, an initial evalua tion of the anti-TSH receptor antibodies (TRAb) [ 1 ] and CD4/CD8 ratio [2] can now be made. It remains to be demonstrated whether the unfavorable prognostic value of high titers of thyroid-stimulating antibodies found by Orgiazzi et al [1] can be extrapo lated to the trade kits estimating TSH-binding inhibitory antibodies.…”
mentioning
confidence: 99%
“…In addition to these clinical features, an initial evalua tion of the anti-TSH receptor antibodies (TRAb) [ 1 ] and CD4/CD8 ratio [2] can now be made. It remains to be demonstrated whether the unfavorable prognostic value of high titers of thyroid-stimulating antibodies found by Orgiazzi et al [1] can be extrapo lated to the trade kits estimating TSH-binding inhibitory antibodies. In the near future, some prospective studies should be under taken to try to identify more precisely the subgroup of patients with GD which repre sents the best indication for ATD [3,4], After an initial period of time (3-6 weeks) where ATD have to be given in high doses (i.e., 60-80 mg/day of carbimazole), the best regimen for the maintenance remains con troversial.…”
mentioning
confidence: 99%